`b)` `[7(2x-5y)(2x+5y)-2(14x^2-3y^2)] : (-3y)`

`b)` `[7(2x-5y)(2x+5y)-2(14x^2-3y^2)] : (-3y)`

2 bình luận về “`b)` `[7(2x-5y)(2x+5y)-2(14x^2-3y^2)] : (-3y)`”

  1. Giải đáp:
    -169/3y
    Lời giải và giải thích chi tiết:
    [7(2x-5y)(2x+5y)-2(14x^2-3y^2)]:(-3y) 
    = [7(4x^2-25y^2)-28x^2+6y^2]:(-3y)
    = (28x^2-175y^2-28x^2+6y^2):(-3y)
    = [(28x^2-28x^2)+(-175+6y^2)]:(-3y)
    = (-169y^2):(-3y)
    = [(-169):(-3)].(y^2:y)
    = -169/3y
    $#<33$

    Trả lời

Viết một bình luận

Câu hỏi mới